Cutting through the value chain: The long-run effects of decoupling the East from the West - Gabriel Felbermayr; Hendrik Mahlkow; Alexander-Nikolai Sandkamp (CESifo GmbH, 2022)
This Policy Brief analyses the long-run effects of an economic decoupling between the political West (i.e. the EU, the US and their allies) and the East (first and foremost Russia and China). A decoupling of Russia from the US and its allies would have much more severe long-term impacts for real income in Russia (minus 9.7 percent) than in the US and its allies (minus 0.2 percent). The reason for the uneven distribution of costs lies primarily in Russia's low economic importance compared with the US and its allies.
Keywords: 330